Pengaruh Kualitas Layanan dan Inovasi Produk Terhadap Kepuasan Anggota Pada Koperasi Danu Artha Tabanan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the effect of service quality and product innovation on member satisfaction at the Danu Artha Tabanan Cooperative. The total population of the study was 322 people and a sample of 76 people with the slovin technique where the sample determination method was by non probability sampling technique. The data analysis techniques used are research instrument tests, namely validity and reliability tests, classical assumption tests and multiple liner regression analysis (T test and F test). Based on the results of the analysis, it was found that: (1) The quality of service has a positive and partially significant effect on member satisfaction. (2) product innovation has a positive and partially significant effect on member satisfaction. (3) service quality and product innovation have a simultaneous positive and significant effect on member satisfaction.